Factors Important in Bank Selection: Empirical Evidences from Customers’ Perspective in Saudi Arabia - Ansari, Zaid Ahmad (Archives of Business Research, 2019)
The main purpose of this study is to find out important factors for consumers in Saudi Arabia to select a bank for their banking needs. Total 300 respondents had participated in this research. A structured questionnaire has been used as research instrument comprising 16 variables on five point Likert Scale intensity. A pilot study has been conducted to refine the survey instrument. Mean, Standard Deviation statistics and Factor Analysis technique has been used to assess the importance of variables. Analysis result shows that all sixteen variables were found important for consumers in selecting a bank. Out of sixteen variables, thirteen variables were found very important with much higher mean value and three were considered important with higher mean value than average. With the help of Factor Analysis Technique Sixteen variables had been group into three factors i.e., i.e., “Product Offerings of the Bank” consisting nine variables, “Service Delivery of the Bank” with five variables and “Banking Institution Type” including two variables respectively. Study findings would be profitable and essential for banking institution in focusing the consumers’ needs and also in making necessary and comprehensive strategy to attract and retain their customers and also to consumers in decision making in selecting a bank for their financial necessities.